"Realizing the problem wasn't necessarily me": the meaning of childhood adversity and resilience in the lives of autistic adults. Issue 1 (31st December 2022) - Heselton, Gabrielle A.; Rempel, Gwen R.; Nicholas, David B.
ABSTRACT: Purpose: There is evidence that childhood adversity is correlated with poor health outcomes across the lifespan. Resilience results when internal and external protective factors in childhood mitigate this relationship. However, among children on the autism spectrum, these relationships are understudied, and little is known about the characteristics and role of adversity and resilience in their in their lives. This study interprets these phenomena as experienced by autistic young adults. Methods: Initially, we conducted community engagement with five members of the autism community who advised on the research question, research design, and analysis. Subsequently, four autistic young adults, three women and one non-binary, aged 19–27, were recruited to participate in semi-structured interviews via phone, video conference, and online chat. Credibility checking interviews followed data analysis. Results: Through interpretative phenomenological analysis we identified themes related to the negative effects of adversity, including social disconnection, mental and emotional well-being, sense of self, and development into young adulthood . Resilience developed in places of refuge and identity and was evident in their transitions into young adulthood . Conclusion: These findings provide direction for decreasing adversity and fostering resilience in children and adolescents on the autism spectrum.